Presence and pathogenic relevance of antibodies to clustered acetylcholine receptor in ocular and generalized myasthenia gravis. - Jacob, S; Viegas, S; Leite, M; Webster, R; Cossins, J; Kennett, R; Hilton-Jones, D; Morgan, B; Vincent, A (2012)
BACKGROUND: Clustered acetylcholine receptor antibodies (clustered AChR-Abs) have been detected in a proportion of patients with previously "seronegative" (SN) generalized myasthenia gravis (GMG), but their presence in patients with ocular MG (OMG) and their pathogenicity in vivo are unknown. OBJECTIVE: To test the presence of clustered AChR-Abs and their pathophysiologic properties in patients with SNMG. DESIGN: Screening and diagnostic tests. SETTING: Regional specialist myasthenia center and clinical laboratory. PATIENTS: Serum samples from 16 patients with SN and OMG were tested for binding to clustered AChRs. Results from 28 further SN patients (14 OMG) were correlated with their single fiber electromyography values. MAIN OUTCOME MEASURES: Presence, complement-fixation capacity, correlation with neurophysiologic changes, and in vivo pathogenicity of clustered AChR-Abs. RESULTS: Up to 50% of patients with previous SN-OMG had complement-fixing IgG1 clustered AChR-Abs. IgG binding (n = 28) and complement deposition (n = 21) each correlated with the mean consecutive difference (jitter) on single-fiber electromyography. Injection of purified IgG from 2 patients with clustered AChR-Abs into wild-type or complement regulator-deficient mice reduced miniature end plate potential amplitudes to an extent similar to that found with AChR-Abs, and complement was deposited at the end plates. A trend was noted toward an increase in the number of packets of acetylcholine released (quantal content). CONCLUSIONS: A proportion of patients with SN-GMG or OMG have clustered AChR-Abs that correlate with their electrophysiologic features. Clustered AChR-Abs can passively transfer disease to mice, demonstrating their pathogenicity, and the mechanisms seem similar to those of patients with typical AChR-Abs.